2021
DOI: 10.14740/jmc3730
|View full text |Cite
|
Sign up to set email alerts
|

An Unusual Case of Intraabdominal Abscess After a Colonoscopy With Polypectomy

Abstract: The use of colonoscopies in the screening of colorectal cancers has helped in the early detection and treatment of these cancers. Less than 0.5% of patients develop colonoscopy complications, mostly bleeding, and less frequently, perforations. There have been very few reported cases of micro-perforations following colonoscopies. We present a case of a 66-year-old female smoker who had undergone a screening colonoscopy for colorectal cancer with two polyps removed 3 weeks prior, who was brought to the hospital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Streptococcus constellatus was reportedly a pathogen in purulent infections including intracranial empyema, liver abscess, pleural effusion, head and neck infections. [12][13][14][15][16] Whereas, few to no studies have reported Streptococcus constellatus leading to multiple pulmonary cavity lesions and vertebral purulent infection. Streptococcus constellatus was considered causing pulmonary infections via aspiration, direct implantation, and hematogenous dissemination.…”
Section: Discussionmentioning
confidence: 99%
“…Streptococcus constellatus was reportedly a pathogen in purulent infections including intracranial empyema, liver abscess, pleural effusion, head and neck infections. [12][13][14][15][16] Whereas, few to no studies have reported Streptococcus constellatus leading to multiple pulmonary cavity lesions and vertebral purulent infection. Streptococcus constellatus was considered causing pulmonary infections via aspiration, direct implantation, and hematogenous dissemination.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism is local mechanical trauma 3 . Intraperitoneal and retroperitoneal abscess formation are also described in a few case reports as a result of colonoscopy 4,5 . As far as we know, there is no report of Rectus Abdominis muscle abscess after colonoscopy.…”
Section: Introductionmentioning
confidence: 99%
“… 3 Intraperitoneal and retroperitoneal abscess formation are also described in a few case reports as a result of colonoscopy. 4 , 5 As far as we know, there is no report of Rectus Abdominis muscle abscess after colonoscopy. In this article, we want to present a case of rectus abdominis muscle abscess after a colonoscopy completed by applying abdominal pressure techniques.…”
Section: Introductionmentioning
confidence: 99%
“…It is usually not considered a pathogen and may be underestimated. In recent years, there are gradually been reported that S. constellatus induces abscesses mainly in brain, mediastina, liver, bone and soft tissues [4][5][6][7][8][9] with the improvement of detection technology. However, there are few reported about HIV/AIDS combined with S. constellatus, although it's reported that this pathogen may cause invasive infections after entering sterile sites in the body, especially in patients with immunosuppression [10].…”
Section: Introductionmentioning
confidence: 99%